2015
DOI: 10.1021/acsnano.5b00230
|View full text |Cite
|
Sign up to set email alerts
|

Flexible One Diode-One Phase Change Memory Array Enabled by Block Copolymer Self-Assembly

Abstract: Flexible memory is the fundamental component for data processing, storage, and radio frequency communication in flexible electronic systems. Among several emerging memory technologies, phase-change random-access memory (PRAM) is one of the strongest candidate for next-generation nonvolatile memories due to its remarkable merits of large cycling endurance, high speed, and excellent scalability. Although there are a few approaches for flexible phase-change memory (PCM), high reset current is the biggest obstacle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 56 publications
0
49
0
Order By: Relevance
“…ZnO is a "rediscovered" semiconductor receiving remarkable interest on behalf of its unique merits and promising technological applications. Currently, the flexible diodes are all fabricated below 200 °C, using either low-temperature-synthesized oxide [27][28][29][30][31][32][33][34][35] and organic [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] materials or high-temperature-prepared Si [52][53][54][55][56][57][58][59][60][61][62][63] and Ge [64] materials combined with transfer method [65], as summarized in Figure 1. The highest reverse voltage or breakdown voltage (Vb) of these flexible diodes are no more than 20 V, with an exception in References 55 and 59 where flexible single-crystalline Si wafers (30 μm thick) were used as the active layers.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO is a "rediscovered" semiconductor receiving remarkable interest on behalf of its unique merits and promising technological applications. Currently, the flexible diodes are all fabricated below 200 °C, using either low-temperature-synthesized oxide [27][28][29][30][31][32][33][34][35] and organic [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] materials or high-temperature-prepared Si [52][53][54][55][56][57][58][59][60][61][62][63] and Ge [64] materials combined with transfer method [65], as summarized in Figure 1. The highest reverse voltage or breakdown voltage (Vb) of these flexible diodes are no more than 20 V, with an exception in References 55 and 59 where flexible single-crystalline Si wafers (30 μm thick) were used as the active layers.…”
Section: Introductionmentioning
confidence: 99%
“…As in the drain current–voltage ( I D – V D ) plot in Figure j, flexible 1 T‐1 R memory presented excellent RS characteristics with mechanical endurance during 1000 iterations of bending. Mun et al also reported a flexible 1 PN diode‐1 PCM (1 D‐1 P) array on a PI substrate using the Si transfer method. In particular, Si‐containing PS‐ b ‐PDMS BCPs were adopted to introduce a SiO x nanostructure between the GST (i.e., phase change material) and the TiN (i.e., heating electrode) reducing the reset power down to a 1/4 level and preventing thermal damage of polymers.…”
Section: Flexible Memristive Devicesmentioning
confidence: 99%
“…However, lower yield of 66% and endurance of 1000 bending cycles for PCRAM are worth examining concerns restricting its practical implementation [23]. Key works on flexible ReRAM and PCRAM are summarized in table I with best performances highlighted.…”
Section: B Memory Management Modulementioning
confidence: 99%